IL-7 and CD4 T Follicular Helper Cells in HIV-1 Infection - Chiodi, Francesca; Bekele, Yonas; Lantto Graham, Rebecka; Nasi, Aikaterini (Frontiers in Immunology, 2017)
IL-7 was previously shown to upregulate the expression of molecules important for interaction of CD4+ T cells with B cells. It is poorly studied whether IL-7 has a role in the biology of T follicular helper (Tfh) cells and if IL-7 dysregulates the expression of B-cell costimulatory molecules on Tfh cells. We review the literature and provide arguments in favor of IL-7 being involved in the biology of human Tfh cells. The CD127 IL-7 receptor is expressed on circulating Tfh and non-Tfh cells and we show that IL-7, but not IL-6 or IL-21, upregulates the expression of CD70 and PD-1 on these cells. We conclude that IL-7, a cytokine which level is elevated during HIV-1 infection, may have a role in increased expression of B cell costimulatory molecules on Tfh cells and lead to abnormal B cell differentiation.